Crop wild relatives of the United States require urgent conservation action - Khoury, Colin K.; Carver, Daniel; Greene, Stephanie L.; Williams, Karen A.; Achicanoy Estrella, Harold Armando; Schori, Melanie; León, Blanca; Wiersema, John H.; Frances, Anne (National Academy of Sciences, 2020)
The contributions of crop wild relatives (CWR) to food security depend on their conservation and accessibility for use. The United States contains a diverse native flora of CWR, including those of important cereal, fruit, nut, oil, pulse, root and tuber, and vegetable crops, which may be threatened in their natural habitats and underrepresented in plant conservation repositories. To determine conservation priorities for these plants, we developed a national inventory, compiled occurrence information, modeled potential distributions, and conducted threat assessments and conservation gap analyses for 600 native taxa. We found that 7.1% of the taxa may be critically endangered in their natural habitats, 50% may be endangered, and 28% may be vulnerable. We categorized 58.8% of the taxa as of urgent priority for further action, 37% as high priority, and 4.2% as medium priority. Major ex situ conservation gaps were identified for 93.3% of the wild relatives (categorized as urgent or high priority), with 83 taxa absent from conservation repositories, while 93.1% of the plants were equivalently prioritized for further habitat protection. Various taxonomic richness hotspots across the US represent focal regions for further conservation action. Related needs include facilitating greater access to and characterization of these cultural-genetic-natural resources and raising public awareness of their existence, value, and plight.